(untitled) (Academic Journal of Internal Affairs, 2020)
The personnel of law enforcement play a pivotal role in reaching the organization’s objectives, both in the field of safe operation and in realizing reintegration efforts. Qualification and know-how of personnel – both educational and psychological – is necessary to reach adequate professional decisions and steps, and optimal solutions in spite of risky conditions. All that lay down special requirements for the organization. This study reviews characteristic competence requirements on law enforcement personnel and their effects and possible consequences in the special work environment. I intend to introduce psychic workload capacity and emotional intelligence in details, as basic competences in public service, with special regard to their role in law enforcement.